3D CFD study of the effect of inlet air flow maldistribution on plate-fin-tube heat exchanger design and thermal–hydraulic performance. (October 2016) - Yaïci, Wahiba; Ghorab, Mohamed; Entchev, Evgueniy
Highlights: Inlet air flow maldistribution in heat exchangers is investigated. 3D CFD simulations are performed for plain-fin-and-tube heat exchangers. Effects of nonuniformity on system design and performance is analysed. CFD simulation is an efficient tool for optimum designs of heat exchanger designs. Abstract: Plate fin-and-tube heat exchangers are used extensively in heating, ventilating, and air conditioning as well as in refrigeration systems. Non-uniform inlet air flow distribution has a substantial effect on heat exchanger performance. Building upon and extending the work of Yaïci et al. (2014), the present study utilises three-dimensional (3D) Computational Fluid Dynamics (CFD) simulations in order to predict the effect of inlet air flow maldistribution on the design and thermal–hydraulic performance of heat exchangers used in air handling units. Computational assessments of the air-side heat transfer and pressure drop characteristics for a variety of inlet air flow distributions and geometrical parameters of staggered plate fin-and-tube heat exchangers were undertaken on heat exchangers with different longitudinal tube pitches, transversal tube pitches, and fin pitches. Characteristics of predicted thermal–hydraulic performance were reported in terms of Colburn j -factor, Fanning friction f -factor, and efficiency index j / f as a function of Reynolds (Re) numbers. The 3D CFD simulations reveal that air flow maldistribution and the effects of geometrical parameters significantly impact the design and performance of heat exchangers. When compared to baseline (i.e., a uniform inlet air velocity profile), substantial fluctuations in the j - and f -factors—deviations as pronounced as 50–70%, 60–66%, and 63–67% for cases with longitudinal tube pitch, transversal tube pitch, and fin pitch variations with non-uniform air flows, respectively—were observed. The 3D CFD method employed by this study has great potential for use in, first, assessments of correlations centred on air flow maldistribution and, second, efforts to optimally design the headers of heat exchangers in order to minimise inlet flow maldistribution and maximise overall system performance.